The effect of diet on vitamin E intake and oxidative stress in response to acute exercise in female athletes - Sacheck, J. M.; Decker, E. A.; Clarkson, P. M. (European Journal of Applied Physiology, 2000)
Vitamin E is the major lipid-soluble antioxidant found in foods, and its bioavailability is affected by the presence of dietary fats. Athletes often consume low-fat diets and may be more susceptible to the oxidative stress produced by exercise due to the low availability of vitamin E. In this study, the effects of a low-fat diet on vitamin E intake and oxidative stress markers were assessed in collegiate female rowers. All subjects habitually consumed either a low-fat (LF; <40 g fat · day-1) or a high-fat (HF; >60 g fat · day-1) diet. Subjects ran downhill for 45 min at 75% of their age-predicted maximal heart rate. Blood samples were collected immediately pre- and post-exercise, and at 6, 24, and 48 h post-exercise. Subjects in the LF group consumed significantly less vitamin E (2.9 mg vitamin E · day-1) than advised by the Recommended Dietary Allowance (RDA; 8.0 mg vitamin E · day-1) and than those in the HF group (9.8 mg vitamin E · day-1; P < 0.05). Plasma concentrations of vitamin E, malondialdehyde, and conjugated dienes were not significantly different between LF and HF before or after exercise. Creatine kinase became significantly elevated above baseline at 6 h and 24 h post-exercise in both groups (P < 0.05). We can conclude from these data that although the subjects in the LF group were not consuming the recommended amount of vitamin E in their diets, their vitamin E intake appears to be sufficient to protect against the oxidative stress produced by this moderate-intensity exercise.